Investigating design parameter effects on the curvature of composite soft actuators by automated numerical simulation with Python integration - Hiep, Trinh Xuan; Phung, Van Binh (Vietnam Journal of Mechanics, 2025)
In the realm of soft robotics, investigating the effect of design parameters on the deformation of complex structures like soft composite actuators is a challenging task. Existing mathematical models often rely on limiting assumptions, while traditional simulation approaches demand substantial computational time and resources, hindering concurrent investigations of multiple design parameters. To address these issues, this paper introduces a new technique to expedite the deformation simulation of composite soft actuators. This automation program enables automatic modification of input parameters while preserving critical properties, constraints, and boundary conditions, resulting in a significant reduction in simulation time. Compared to traditional methods requiring approximately 60 minutes for a single task, our technique achieves the same in merely 10 minutes. The developed program is applied to analyze the impact of design parameters on the curvature of composite soft actuators, leading to the identification of optimal parameters. Through experimental verification, the reliability and efficiency of our technique are demonstrated, showing simulation results with less than a 10% error when compared to physical experiments. The proposed approach enables swift investigation of design parameter influence, facilitating the identification of optimal soft robotic structures for specific objectives. As a result, it has the potential to become a promising tool for advancing soft robotics design and analysis.